2018
DOI: 10.1080/14786419.2018.1475377
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula x intermedia and Lavandula angustifolia essential oils: phytochemical composition and antimicrobial activity against foodborne pathogens

Abstract: Four cultivars (cv) of Lavandula x intermedia ('Abrialis', 'Alba', 'Rinaldi Ceroni' (R.C.) and 'Sumiens') were cultivated in Italy and their essential oils (EOs) were distilled from Alfalfa Mosaic Virus-free plants. These EOs and one from L. angustifolia Miller were chemically characterised by GC-MS and GC-FID. Antimicrobial activity was evaluated against Listeria monocytogenes (24 strains) and Salmonella enterica (10 food strains). Minimal inhibitory concentrations (MIC) ≥ 10.0 μL/mL inhibited Salmonella (cv … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 15 publications
(13 reference statements)
4
34
0
4
Order By: Relevance
“…[3] Its commercial value is mainly linked to the presence of glandular trichomes, responsible for the production of an amazing diversity of volatile substances. [4][5][6][7] The literature proposed two previous micromorphological studies on leaves and flowers, both focused on the characterization of anatomical markers, including trichomes. [3,8] In the phytochemical field, works about the characterization of volatile organic compounds (VOCs) emitted by leaves and flowers are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Its commercial value is mainly linked to the presence of glandular trichomes, responsible for the production of an amazing diversity of volatile substances. [4][5][6][7] The literature proposed two previous micromorphological studies on leaves and flowers, both focused on the characterization of anatomical markers, including trichomes. [3,8] In the phytochemical field, works about the characterization of volatile organic compounds (VOCs) emitted by leaves and flowers are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…L. x intermedia EO showed a composition rich in linalool (36.0%), linalyl acetate (27.3%). Other peculiar constituents of this hybrid were camphor (5.9%), 1,8-cineole (5.0%), and borneol (4.0%) [ 28 , 29 ]. M. arvensis EO main compounds included menthol (73.8%), menthone (7.8%), isomenthone (5.4%), limonene (3.6%), and menthyl acetate (2.1%).…”
Section: Resultsmentioning
confidence: 99%
“…The screening of medical plants, and in particular of those rich in EOs, for antibacterial and antifungal activities is important to find new active antimicrobial compounds. Many studies on the antibacterial activity of Lavandula EOs have been based on Lavandula angustifolia Miller [ 29 , 33 ], even if other varieties, such L. x intermedia , have shown therapeutic potential [ 34 ]. Lavandula species have also demonstrated to be a weapon against antimicrobial resistant pathogens responsible for human infections [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported high antibacterial activity of the essential oils, compared to synthetic antibacterial compounds. The low antimicrobial activity of single EO components has been often observed, as the mechanism of action of EOs is multi-component, since the whole phytocomplex could simultaneously attack different targets within the cell, with a final result not explainable by a simple additive effect (Tardugno et al 2018).…”
Section: Antimicrobial Activitymentioning
confidence: 99%